Drug/Lead Compound Hydroxymethylation as a Simple Approach to Enhance Pharmacodynamic and Pharmacokinetic Properties - Santos, Soraya S.; Gonzaga, Rodrigo V.; Scarim, Cauê B.; Giarolla, Jeanine; Primi, Marina C.; Chin, Chung M.; Ferreira, Elizabeth I. (Frontiers in Chemistry, 2022)
Hydroxymethylation is a simple chemical reaction, in which the introduction of the hydroxymethyl group can lead to physical–chemical property changes and offer several therapeutic advantages, contributing to the improved biological activity of drugs. There are many examples in the literature of the pharmaceutical, pharmacokinetic, and pharmacodynamic benefits, which the hydroxymethyl group can confer to drugs, prodrugs, drug metabolites, and other therapeutic compounds. It is worth noting that this group can enhance the drug’s interaction with the active site, and it can be employed as an intermediary in synthesizing other therapeutic agents. In addition, the hydroxymethyl derivative can result in more active compounds than the parent drug as well as increase the water solubility of poorly soluble drugs. Taking this into consideration, this review aims to discuss different applications of hydroxymethyl derived from biological agents and its influence on the pharmacological effects of drugs, prodrugs, active metabolites, and compounds of natural origin. Finally, we report a successful compound synthesized by our research group and used for the treatment of neglected diseases, which is created from the hydroxymethylation of its parent drug.